Ethics and ethical behaviour - Syed Abdullah Idid, Syed Arabi (2020)
Ethics and Values are fundamental in providing the environment for sustainable development. One must however, recognise the various levels of ethical practice. For example in the university, there are ethics prescribed for students, academics and non-academics. At the same time one must also remember that there are also ethics for different professions. There are ethical practices reflected in the code of ethics prescribed for judges, lawyers, medical practitioners, accountants and civil servants. Professional bodies are serious in their code of ethics and will set up disciplinary boards to put on trial members who have bridged the ethical behaviour or standard. But these ethical standards are meant for members only and in many instances do not have the force of law beyond the organisation. Another matter that merits our attention is the lack of case studies on ethics. We have been prompted to prescribe and provide the norms of ethical behaviour but we have not taken on ourselves to do case studies on whether these norms are being practised and how they may give way to abuse. Having case studies would allow a general feeling how these ethics have clear relevance in society.